2013
DOI: 10.1021/ed4001409
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth Crystals: Preparation and Measurement of Thermal and Electrical Properties

Abstract: We describe a laboratory experiment that serves as an introduction to solid-state and materials science, a topic that requires additional attention in the undergraduate chemistry laboratory curriculum. The experiment illustrates the longrange translational order, crystal growth, and the macroscopic manifestations of that order. This is demonstrated through the preparation and characterization of large, well-formed bismuth crystals, an aesthetically pleasing product. The characterization of the grown bismuth cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Here we report a new laboratory activity for students to engage with chemistry concepts like solubility, acid–base chemistry, colorimetric assays, and redox reactions using everyday items. This activity could be expanded to teach other chemistry lessons like gravimetric analysis, equilibrium, bioavailability, crystallinity and crystal growth, electrolysis, color, and other medicinal chemistry topics . Investigating common medications encourages students to reflect on content of medications, encourages critical thinking about health decisions, and promotes implementing problem solving strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Here we report a new laboratory activity for students to engage with chemistry concepts like solubility, acid–base chemistry, colorimetric assays, and redox reactions using everyday items. This activity could be expanded to teach other chemistry lessons like gravimetric analysis, equilibrium, bioavailability, crystallinity and crystal growth, electrolysis, color, and other medicinal chemistry topics . Investigating common medications encourages students to reflect on content of medications, encourages critical thinking about health decisions, and promotes implementing problem solving strategies.…”
Section: Discussionmentioning
confidence: 99%
“…If this laboratory method is utilized in an upper-division setting, additional experiments may be performed on a large sample of pure bismuth metal. Milán et al demonstrated a method for the synthesis and characterization of bismuth crystals in an undergraduate laboratory setting …”
Section: Methodsmentioning
confidence: 99%
“…Milań et al demonstrated a method for the synthesis and characterization of bismuth crystals in an undergraduate laboratory setting. 12 ■ HAZARDS Approved safety goggles, nitrile-based gloves, and standard laboratory personal-protective equipment must be worn at all times while this experiment is performed. Hydrochloric acid and sodium phosphate can cause severe caustic burns.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Up to now, there have been few experiments on the basic processes and principle of crystal growth recommended for the undergraduate curriculum, much less integrated laboratory experiments with the concepts and techniques of crystal growth and characterization. It is important and necessary to add comprehensive research-based experiments to undergraduate courses, which will encourage students to conjugate their thinking between different subjects and prevent segmented thinking. Herein, a comprehensive laboratory involving single crystal growth, the basic characterization of structures and properties, and analyses of the structure–property relationship was designed to introduce students to the current research techniques being used in crystal materials and to deepen their knowledge of crystals, one of the most important solid-state materials.…”
Section: Introductionmentioning
confidence: 99%